Job Demands and Exposure to Workplace Bullying: A Study of State Universities in Sri Lanka - T.J.R, Thisera; N.N.J, Nawaratne (Asian Journal of Empirical Research, 2018)
Workplace bullying is one of main mistretaments at work that has many negative impacts over individuals, groups, organizations and the larger society. The present study investigates the impact of job demands (i.e., cognitive and emotional demands) on exposure to workplace bullying based on the work environment hypothesis in higher education sector in Sri Lanka and the mediating effect of emotional exhaustion over the relationship between job demands and exposure to workplace bullying using the three way model. Survey data were collected from 203 academics attached to management faculties in state universities in Sri Lanka using a self-administered questionnaire. Hypothesized model was tested through simple linear regression analysis and mediator analysis. Based on the results, the study provides evidence for the existence of workplace bullying in state university sector in Sri Lanka. Further, it reveals that cognitive, emotional and aggregate job demands have significant impact on exposure to workplace bullying. Further, it found that relationship between these job demands and exporsure to workplace bullying are partially mediated by emotional exhaustion. The study provides numerous theoretical and practical implications.